Laser beam shaping applications - Dickey, Fred M., 1941-; Lizotte, Todd E. (Optical engineering, 2017)
"Since the advent of the laser, many applications have required shaping the laser beam irradiance profile. A few of the primary applications include material processing, including welding, cutting, and drilling; and medical procedures, such as corneal surgery and cosmetic skin treatments. Other applications include laser/material interaction studies, lithography, semiconductor manufacture, graphic arts, optical data processing, and military uses. Laser Beam Shaping Applications is a companion to Laser Beam Shaping: Theory and Techniques. It treats in detail how laser beam shaping is implemented in several major applications"--